2007
DOI: 10.1111/j.1530-0277.2007.00549.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Alcohol Accentuates Simian Acquired Immunodeficiency Syndrome‐Associated Wasting

Abstract: Background-Survival following human immunodeficiency virus (HIV) infection has improved significantly following the advent of highly active antiretroviral therapy. A large percentage of HIV-infected patients consume and abuse alcohol. Erosion of lean body mass is an important contributing factor to patient morbidity and mortality, and is a common feature of both chronic alcohol (ALC) consumption and acquired immunodeficiency syndrome (AIDS). We hypothesized that alcohol-induced loss in lean body mass is likely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
71
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(78 citation statements)
references
References 55 publications
(59 reference statements)
7
71
0
Order By: Relevance
“…All cell-based experiments were performed in BSL2 laboratory facilities at LSUHSC-NO. Animals were administered alcohol or sucrose intragastrically as previously described (5,24). Briefly, animals were administered alcohol (13-14 g of ethanol per kilogram body wt per week; 30% wt/vol water) or sucrose for 19 mo via a surgically implanted catheter.…”
Section: Experimental Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…All cell-based experiments were performed in BSL2 laboratory facilities at LSUHSC-NO. Animals were administered alcohol or sucrose intragastrically as previously described (5,24). Briefly, animals were administered alcohol (13-14 g of ethanol per kilogram body wt per week; 30% wt/vol water) or sucrose for 19 mo via a surgically implanted catheter.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…These cells are quiescent during adulthood but can enter into cell cycle upon stimulation to repair damaged muscle by proliferation, differentiation, and fusion with existing myofibers (39). Our previous studies with chronic binge alcohol (CBA)-fed, Simian immunodeficiency virus (SIV)-infected rhesus macaques have shown that chronic alcohol consumption promotes a prooxidative and proinflammatory skeletal muscle milieu in SIV-infected animals, and this is associated with accentuated wasting at end-stage SIV infection (21,24). The inflammatory environment in skeletal muscle would be expected to activate quiescent SCs to proliferate and differentiate into myotubes to compensate for enhanced skeletal muscle proteolysis (39,45).…”
mentioning
confidence: 97%
“…25,26 More recent simian studies have provided evidence that chronic alcohol intake prior to and during HIV infection results in a higher viral set point, more rapid progression to end-stage disease, and exacerbation of the AIDS wasting syndrome through increased expression of tumor necrosis factor-a and atrogin-1. [27][28][29] Several studies on alcohol and HIV disease progression after the introduction of antiretroviral therapy (ART) have established that alcohol results in reduced viral load response and CD4 þ cell reconstitution, and poorer adherence to ART. [30][31][32] A cross-sectional analysis of HIV-1-infected drug users found that heavy alcohol users (defined as alcohol intake three to four or more times per week), who were receiving highly active antiretroviral therapy (HAART), were four times less likely to achieve undetectable viral load and two times more likely to have CD4 þ cell counts below 500 cells=ml than moderate drinkers or abstainers.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the experimental simian immunodeficiency virus infection of macaque monkeys shows a decrease in body weight gain; however, although it allows for better control of nutritional variables than human studies, its use is limited by its expense (32,33). In contrast, several lines of transgenic (Tg) rodents, both mice and rats, that are noninfectious and express one or more of the HIV-1 viral envelope proteins have been developed (39,41).…”
mentioning
confidence: 99%